Interferences between natural and anthropic hazards in marine-coastal environments: Assessing transport from land to the offshore systems in the Crotone basin (Ionian Sea). (5th July 2022) - Oliveri, Elvira; Ausili, Antonella; Barsanti, Mattia; Conte, Fabio; Delbono, Ivana; Del Core, Marianna; Giaramita, Luigi; Passaro, Salvatore; Placenti, Francesco; Quinci, Enza Maria; Romano, Elena; Sabatino, Nadia; et al.
Abstract: This paper is focused on the field-evidence of environmental hazard associated with flood events in highly contaminated marine coastal areas. The Crotone site (Ionian Sea), in the 1900s hosted a large industrial settlement (with the largest plant in Europe of zinc production, phosphorus manufacture, etc.) which left a severe legacy of environmental pollution. Here, we report the results of an investigation related to the distribution of heavy metals (Zn, Pb, Cd, Cu) in 230 sediment cores that allowed a detailed reconstruction of the contamination due to the discharge at sea of industrial wastes deriving from the Zn-sulphides leaching processes. High concentrations of heavy metals (e.g., Zn > 5000 mg kg −1 ) accumulated in sediments of the seabed along coastline, exposed to the fluvial and coastal dynamics, act as a potential long-term source of pollution for the marine ecosystem. Fingerprints of historically flash flood events evidenced in two 210 Pb dated sediment cores suggest that these catastrophic events played a crucial role in the land-to-sea transferring (and sequent dispersing effects) of highly polluted sediments. Anomalous depositions of heavy metals-rich sediments in the offshore system (4–6 km from the coastline) testify secondary contamination due to mobilization and redistribution of old contaminated sediment due to flood events. These interactions between natural and anthropic hazards trigger cumulative mechanisms of multiple-pollution and transfer of contamination from polluted nearshore to offshore nearly pristine areas trough main canyon axes. Graphical abstract: Image 1 Highlights: Historically polluted sediments affect the status of the Crotone marine coastal area. Flood events remobilize and redistribute polluted sediments in the offshore. 210 Pb dated sedimentary records document multiple episodes of flooding on-land. Extreme events amplify effects of pollution in the coastal system.